Development of modified diagnostic criteria for bacterial vaginosis at peripheral health centres in developing countries - Mittal, Vineeta; Jain, Amita; Pradeep, Yashodhara (The Journal of Infection in Developing Countries, 2011)
Introduction: Bacterial vaginosis (BV) is the commonest cause of abnormal vaginal discharge in women of child-bearing age and is associated with increased susceptibility to HIV-AIDS and sexually transmitted diseases. In obstetrics, BV has been implicated in causing various complications. In clinical practice, BV is diagnosed using Amsel criteria and Nugent scoring. Using modified Amsel criteria, we determined that the fulfilling of any two instead of three criteria can be diagnostic of BV. Methodology: This prospective cross-sectional study involved pregnant females complaining of excessive vaginal discharge admitted in a tertiary health centre in central India. Four vaginal swabs were collected for the diagnosis of BV by Amsel criteria, modified Amsel criteria, and Nugent scoring on Gram stain. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of each individual criterion and combinations of criteria were calculated by using Nugent scoring as the gold standard and by chi square test. Results: In the present study overall prevalence of BV was 12%. The sensitivity of individual or a combination of two criteria was almost same or higher than that of Amsel criteria. Specificity of each combination of criteria was comparable to that of Amsel criteria. However, a combination of high pH and amine odor test had the highest sensitivity (88%) and highest PPV (62%). Diagnostic accuracy of all combinations in our study was equal to or slightly higher than that of Amsel criteria. Conclusion: Diagnostic accuracy of new modified Amsel criteria is as reliable as that of Amsel criteria.